A cross sectional study on Psychological aspects and Quality of Life of Nursing Students (Kerala Journal of Psychiatry, 2020)
Background: With the increase in students pursuing nursing education in India, studies report one in four students suffer from stress related disorders like anxiety and depression. While many studies focus on the stressors and associated external factors, this study was designed to assess dimensions of personality, types of coping and potential impact on quality of life.Methodology: A cross sectional survey was conducted with universal sampling of 161 consenting nursing students. Semi structured proforma, Eysenck Personality Inventory (EPI), Coping Strategies Inventory- short form (CSI-SF) and WHOQOL – BREF were used for data collection. Statistical analysis was done using SPSS version 20. Descriptive statistics of mean (sd) and percentages and inferential statistics of Independent t-test, ANOVA and Pearson’s correlation analysis were used.Results: 161 out of 184 study participants were included in the analysis. 93.2% of participants were females and more than 60% were from rural background. Neuroticism scores were significantly higher among first and second year student. Problem focused disengagement and emotion focused disengagement scores were significantly higher among first and fourth year students respectively. Third year students scored high across psychological, social and environmental domains of quality of life.Conclusion: Neuroticism as a trait negatively impacts the student’s coping strategies and quality of life. Early understanding of individual’s personality will help to implement measures to strengthen their coping strategies in dealing with stressors and improve quality of life.
Keywords: Personality; Coping Strategies; Quality of Life; Nursing students